Indicator, symbol and acronym in automotive interior: the understanding of design and interaction with drivers / Mohd Taufik Zulkefli - Zulkefli, Mohd Taufik (2014)
Indicator, symbol or typefaces are a way of interaction or communication between drivers and cars. Located mostly on the instrument cluster, it will indicate usage of some features or function such as handbrake, lamps and doors. It also function as an alert to the driver on the malfunction of some components or car current condition for them to gives attention, check or replace such as ABS system, fuel level and battery conditions. Therefore the research objective tend to look into the effectiveness of those indicator, symbol and acronym, the driver understanding of those, and also to educate the important of those indicator, symbol and acronym to the driver. The quantitative approached were employed to gained data from the participant. The introducing of new features inside cars is also contributed to the existence of new sign and symbol on instrument cluster. However many drivers didn't realize the important use of this indicator and symbol In fact, the indicator and symbol not only represent the function of some features in the car but also as an early reminder for them about condition of their cars. Many drivers tend to ignore the important of sign and symbol even though it's indicates a situation such as buckle up seat belt, door not closed properly and fuel empty. Many drivers also didn't know meaning behind those sign and symbol because they aren't referring to the owner's manual provided especially when buying new cars. For some drivers who understand those indicator and symbol, they were confusing when some symbol is different in some model of cars but represents a same meaning. This research investigates on the interaction between drivers and the indicator and symbol on the instrument cluster and the problem encountered while driving. It was focused on the knowledge, a possibility of confusion that may occur among drivers when some indicator or symbol having a different design but indicates a same meaning and also a possibility of distraction when too many symbol especially new symbol appear on the instrument cluster. Results in this research prove that this kind of things can cause unwanted things such as road accident and emotional stress to the driver in the long term. Regarding to this research result, it may give a benefit to the automotive manufacturer to revise a usage of indicator and symbol that can be more user friendly and also raise awareness among drivers the importance of those indicator and symbol to assist them while driving.